Research on the Impact and Utility of Rural Revitalization Big Data Service on Farmers Based on Integrated Technology Acceptance Model - Zhao, Shiyuan; Wang, Lin; Cai, Donghong (Mathematical problems in engineering, 2022)
The integrated technology acceptance model was proposed in 2003 and has been gradually applied in many fields since then. At present, the promotion of agricultural big data has achieved initial results, and a number of agricultural big data practice demonstration projects have been formed. For example, Shandong Province supports the establishment of the “Big Data Platform of Bohai Granary Science and Technology Demonstration Project,” which includes four modules of data collection, mining and analysis, monitoring and early warning, and decision-making service. It is characterized by the diversity of massive data sources, the integration of historical and real-time data, and multifactor comprehensive analysis and decision making. However, farmers, as an important service subject of agricultural big data platform, do not have strong willingness to participate. In the era of big data, it is still difficult for farmers to obtain data information and services, and their ability to obtain, screen, and use data is poor. Therefore, it is of great practical significance to effectively improve farmers’ willingness to adopt and use agricultural big data. Based on the integrated technology acceptance model, this study analyzed the impact of big data service of rural revitalization on farmers. Firstly, the basic content of integration technology acceptance theory was analyzed, and the research hypothesis was proposed based on this theory. After that, the questionnaire survey was used to empirically analyze the impact of big data service on farmers. Reliability and validity test, correlation test, goodness of fit test, and path system test were carried out on the analysis results to prove the factors that affect farmers’ behavior and attitude of using big data.